Targeted next-generation sequencing of 50 cancer-related genes in Japanese patients with oral squamous cell carcinoma - Takafumi Nakagaki; Miyuki Tamura; Kenta Kobashi; Akina Omori; Ryota Koyama; Masashi Idogawa; Kazuhiro Ogi; Hiroyoshi Hiratsuka; Takashi Tokino; Yasushi Sasaki (Tumor Biology)
Somatic mutation analysis is a standard of practice for human cancers to identify therapeutic sensitization and resistance mutations. We performed a multigene sequencing screen to explore mutational hotspots in cancer-related genes using a semiconductor-based sequencer. DNA from oral squamous cell carcinoma samples was used as a template to amplify 207 regions from 50 cancer-related genes. Of the 80 oral squamous cell carcinoma specimens from Japanese patients, including formalin-fixed paraffin-embedded samples, 56 specimens presented at least one somatic mutation among the 50 investigated genes, and 17 of these samples showed multiple gene somatic mutations. TP53 was the most commonly mutated gene (50.0%), followed by CDKN2A (16.3%), PIK3CA (7.5%), HRAS (5.0%), MET (2.5%), and STK11 (2.5%). In total, 32 cases (40.0%) were human papillomavirus positive and they were significantly less likely to have a TP53 , mutation than human papillomavirus–negative oral squamous cell carcinomas (8/32, 25.0% vs 32/48, 66.7%, p = 0.00026). We also detected copy number variations, in which segments of the genome could be duplicated or deleted from the sequencing data. We detected the tumor-specific TP53 mutation in the plasma cell-free DNA from two oral squamous cell carcinoma patients, and after surgery, the test for these mutations became negative. Our approach facilitates the simultaneous high-throughput detection of somatic mutations and copy number variations in oral squamous cell carcinoma samples.